2009
DOI: 10.1111/j.1365-2095.2008.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Distal intestinal gene expression in Atlantic salmon (Salmo salarL.) fed genetically modified maize

Abstract: In the current experiment, RNA was isolated from the distal intestine (DI) of Atlantic salmon-fed fishmeal-based diets containing either genetically modified (GM) maize (Bt maize, Mon810 Ò , Monsanto Company, St. Louis, Missouri, USA) or its conventional near-isogenic parental line (non-GM) for 82 days, both at 300 g kg )1 inclusion. From a suppression subtractive hybridization (SSH) cDNA library, 192 clones with similarity to both known and novel Atlantic salmon sequences were identified. Real-time PCR was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Studies relevant to nutritionally related immune gene expression have been conducted for gilthead sea bream (Reyes‐Becerril et al ; Montero et al ; Reyes‐Becerril et al , ; Calduch‐Giner et al ; Cerezuela et al ), but none of these concerned the effect of FM substitution by soybean protein. For this purpose, six immune‐ and stress protein‐related genes, previously described in gilthead sea bream (Reyes‐Becerril et al ) and in several other species, like Atlantic cod, Gadus morhua , Atlantic salmon and Atlantic halibut, Hippoglossus hippoglossus (Hansen et al ; Olsen et al ; Sagstad et al ; Frøystad‐Saugen et al ; Lilleeng et al ; Murray et al ; Skugor et al ) were selected to examine the effect of the soybean protein on immune and stress protein responses. The expression of these genes was evaluated in HK and distal intestine due to their implication in fish immune functions (Press and Evensen ; Tort et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies relevant to nutritionally related immune gene expression have been conducted for gilthead sea bream (Reyes‐Becerril et al ; Montero et al ; Reyes‐Becerril et al , ; Calduch‐Giner et al ; Cerezuela et al ), but none of these concerned the effect of FM substitution by soybean protein. For this purpose, six immune‐ and stress protein‐related genes, previously described in gilthead sea bream (Reyes‐Becerril et al ) and in several other species, like Atlantic cod, Gadus morhua , Atlantic salmon and Atlantic halibut, Hippoglossus hippoglossus (Hansen et al ; Olsen et al ; Sagstad et al ; Frøystad‐Saugen et al ; Lilleeng et al ; Murray et al ; Skugor et al ) were selected to examine the effect of the soybean protein on immune and stress protein responses. The expression of these genes was evaluated in HK and distal intestine due to their implication in fish immune functions (Press and Evensen ; Tort et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have been taken to make the utilization of plant protein by different fish more efficient, including the improvement of genetic selection in plants aiming to reduce the effect of anti-nutritional components and the stimulation of the intestinal microbiota of fish ( Bakke-McKellep et al, 2007 ; Froystad-Saugen et al, 2009 ; Merrifield et al, 2009 ). Additionally, the diversification of new protein ingredients (from animals and plants), and identification of additives (natural or synthetic) with “intestinal protective” activity to promote growth and health have been made a priority ( Refstie et al, 2010 ; Sicuro et al, 2010 ; Czubinski et al, 2014 ).…”
Section: Aquaculture Nutrition: Trends and Future Perspectivementioning
confidence: 99%
“…Sissener et al (2011) reported further details on a previously performed feeding study in Atlantic salmon supplied diets containing 30% maize MON 810 and a near-isogenic parental maize line (non-GM). It was reported that the level of deoxynivalenol (DON) differed between the materials from MON 810 and the comparator used for feed preparation, which, according to the same investigators, might account for the previously observed differences in growth, relative organ sizes, cellular stress and intestinal cell gene expression (e.g., Frøystad-Saugen et al, 2009) as well as in immunological parameters in Atlantic salmon exposed to maize MON 810 as compared to the conventional counterpart. Guertler et al (2012) slaughtered ten cows fed maize MON 810 and seven cows fed control maize and studied the gene expression in tissues of the gastrointestinal tract and the liver.…”
Section: Results From the Literature Search A) Toxicological And Nutrmentioning
confidence: 99%
“…A number of publications on animal feeding studies with maize MON 810 have become available since the last opinion on this maize by the EFSA GMO Panel. These feeding studies included maize MON 810 grain and grain of the appropriate comparator in the diets of broilers (Řehout et al, 2009;Swiatkiewicz et al, 2010a), Japanese quails (Sartowska et al, 2012), lactating cows (Guertler et al, 2009(Guertler et al, , 2010Paul et al, 2010;Steinke et al, 2010), pigs (Delgado and Wolt, 2010;Rossi et al, 2011;Stadnik et al, 2011;Swiatkiewicz et al, 2011;Buzoianu et al, 2012a,c;Walsh et al, 2012a), and Atlantic salmon (Frøystad-Saugen et al, 2009;Sissener et al, 2011). Rossi et al (2011) noted that piglets supplied maize MON 810 performed better than piglets supplied the control maize and suggested that this difference was due to the lower level of fumonisin B1 in the diet.…”
Section: Results From the Literature Search A) Toxicological And Nutrmentioning
confidence: 99%